Calidad del servicio y determinantes de la satisfacción en usuarios de los servicios hospitalarios de Cartagena de Indias, Colombia; Perceived quality and determining the satisfaction in users of hospital services in Cartagena, Colombia - Juan Carlos Vergara Schmalbach; Víctor Manuel Quesada Ibargüen; Francisco Javier Maza Ávila (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2018)
– Quality of Service and User Satisfaction in Health System form a topic with academic and managerial importance. Knowledge on variables that influence this indicator will help guide the strategies and/or actions aimed at improving service. In this sense, the goal of this article consists in assessing the hospital service quality in the city of Cartagena de Indias, Colombia, from users' viewpoint (by considering the dimensions of Physical Infrastructure, Coverage and Access) in order to identify the determinants of service quality and satisfaction. This paper charts the development of an empirical case by using the multivariate technique named Partial Least Squares (PLS), which belongs to the family of methods known as Structural Equation Modeling (SEM). The results show positive effect of those variables into service quality and overall satisfaction. It is concluded that infrastructure, access and coverage are key factors to: a) characterize the hospital service in the city of Cartagena de Indias; and b) contribute to strengthening users' confidence and fidelity.
Keywords: C12; C35; I18; J28; 330; Service quality; satisfaction; health service; Partial Least Squares regression